Development of Self-Learning Material for Difficult Units in the Subject ‘Fundamentals of Nomenclature’ for 11th Grade — Complete Gujarati Academic Draft : અગિયારમું ધોરણના નામાનાં મૂળતત્ત્વો વિષયના કઠિન એકમો માટે સ્વ-અધ્યયન સાહિત્યની રચના — નો સંપૂર્ણ ગુજરાતી એકેડેમિક ડ્રાફ્ટ તૈયાર કરીએ - Vaja, Ravikumar Mohanbhai; Dodiya, Malabhai B (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The primary objective of the present research was to develop Self-Learning Material (SLM) for the difficult units of the 11th grade subject “Fundamentals of Nomenclature” and to describe its structural features. The importance of self-learning material in the field of education is steadily increasing, especially when it becomes necessary to provide students with supplementary, well-structured, and independent learning resources in addition to textbooks. In the first phase of the study, difficult units of the subject were identified through a survey conducted among students and subject experts. Subsequently, self-learning material was developed for the selected units, incorporating simplified language, examples, diagrams, practice questions, and self-assessment components in a sequential manner. This material was then submitted to subject experts for validation, and the suggested modifications were incorporated into the final version. The results of the study indicate that the developed self-learning material, due to its inclusion of visual-based learning, clear structure, and practice exercises, can be effective in simplifying difficult units. This study can serve as a guide for teachers, student-teachers, and educational content developers. Abstract in Gujarati Language: વર્તમાન સંશોધનનો મુખ્ય ઉદ્દેશ અગિયારમું ધોરણના "નામાનાં મૂળતત્ત્વો" વિષયના કઠિન એકમો માટે સ્વ-અધ્યયન સાહિત્ય (Self-Learning Material– SLM)નું વિકાસ અને તેની રચનાત્મક વિશેષતાઓનું વર્ણન કરવાનું હતું. શૈક્ષણિક ક્ષેત્રમાં સ્વ-અધ્યયન સાહિત્યનું મહત્વ વધતું જાય છે, ખાસ કરીને ત્યારે જ્યારે વિદ્યાર્થીઓને પાઠ્યપુસ્તક સિવાય પણ સરળ, ગોઠવેલ અને સ્વતંત્ર રીતે અભ્યાસ કરી શકે તેવું સાહિત્ય ઉપલબ્ધ કરાવવું જરૂરી બને છે. અભ્યાસમાં પ્રથમ તબક્કામાં વિષયના કઠિન એકમોની ઓળખાણ વિદ્યાર્થીઓ અને વિષય નિષ્ણાતોના સર્વે દ્વારા કરવામાં આવી. ત્યારબાદ, પસંદ કરાયેલા એકમો માટે ક્રમશઃ સરળ ભાષા, ઉદાહરણો, આકૃતિઓ, અભ્યાસપ્રશ્નો, તથા સ્વ-મૂલ્યાંકન ઘટકો સહિતનું સ્વ-અધ્યયન સાહિત્ય તૈયાર કરવામાં આવ્યું. આ સામગ્રીને વિષય નિષ્ણાતો દ્વારા માન્યતા માટે રજૂ કરવામાં આવી અને સૂચિત ફેરફારોને અંતિમ આવૃત્તિમાં સામેલ કરવામાં આવ્યા. અભ્યાસના પરિણામો સૂચવે છે કે વિકસાવેલ સ્વ-અધ્યયન સાહિત્યમાં દૃશ્ય-આધારિત શીખણ, સ્પષ્ટ માળખું અને અભ્યાસકસરતોના સમાવેશને કારણે તે કઠિન એકમોને સરળ બનાવવામાં અસરકારક સાબિત થઈ શકે છે. આ અભ્યાસ શિક્ષકો, શિક્ષણવિદ્યાર્થીઓ અને શૈક્ષણિક સામગ્રી વિકાસકર્તાઓ માટે માર્ગદર્શકરૂપ બની શકે છે. Keywords: સ્વ-અધ્યયન સાહિત્ય, નામાનાં મૂળતત્ત્વો, અગિયારમું ધોરણ, કઠિન એકમો, શૈક્ષણિક સામગ્રી વિકાસ, દૃશ્ય આધારિત શીખણ